A MicroRNA93-IRF9-IRG1-Itaconic Acid Pathway Modulates M2-like-Macrophage Polarization to Revascularize Ischemic Muscle - Ganta, Vijay Chaitanya (Circulation, 2017)
BACKGROUND: Currently no therapies exist for treating, and improving outcomes in patients with severe peripheral arterial disease (PAD). MicroRNA93 (miR93) has been shown to favorably modulate angiogenesis and reduce tissue loss in genetic PAD models. However, the cell specific function, downstream mechanisms or signaling involved in miR93 mediated ischemic muscle neovascularization is not clear. Macrophages were best known to modulate arteriogenic response in PAD and the extent of arteriogenic response induced by macrophages is dependent on greater M2 to M1-activation/polarization state. In the current study, we identified a novel mechanism by which miR93 regulates macrophage-polarization to promote angiogenesis and arteriogenesis to revascularize ischemic muscle in experimental-PAD. METHODS: In vitro (macrophages, endothelial cells, skeletal muscle cells under normal and hypoxia serum starvation (HSS) conditions) and in vivo experiments in preclinical-PAD models (unilateral femoral artery ligation and resection)) were conducted to examine the role of miR93-interferon regulatory factor-9 (IRF9)-immune responsive gene-1 (IRG1)-itaconic acid pathway in macrophage-polarization, angiogenesis, arteriogenesis and perfusion recovery. RESULTS: In vivo, compared to wild type (WT) controls, miR106b-93-25 cluster deficient mice (miR106b-93-25(−/−)) showed decreased angiogenesis and arteriogenesis correlating with increased M1-like-macrophages following experimental-PAD. Intra-muscular delivery of miR93 in miR106b-93-25(−/−) PAD mice increased angiogenesis, arteriogenesis, the extent of perfusion which correlated with more M2-like-macrophages in the proximal and distal hind-limb muscles. In vitro, miR93 promotes and sustains M2-like-polarization even under M1-like-polarizing conditions (HSS). Delivery of bone marrow derived macrophages from miR106b-93-25(−/−) to WT ischemic-muscle decreased angiogenesis, arteriogenesis and perfusion, while transfer of wild-type macrophages to miR106b-93-25(−/−) had the opposite effect. Systematic analysis of top-differentially upregulated genes from RNA-sequencing between miR106b-93-25(−/−) and WT ischemic-muscle showed that miR93 regulates IRG1 function to modulate itaconic acid production and macrophage-polarization. 3′UTR luciferase-assays performed to determine whether IRG1 is a direct target of miR93 revealed that IRG1 is not a miR93 target but IRF9 that can regulate IRG1-expression is a miR93 target. In vitro, increased expression of IRF9, IRG1 and itaconic acid treatment significantly decreased endothelial angiogenic potential. CONCLUSION: We conclude that miR93 inhibits IRF9 to decrease IRG1-itaconic acid production to induce M2-like-polarization in ischemic muscle to enhance angiogenesis, arteriogenesis and perfusion recovery in experimental-PAD.